Association of Daily Dietary Intake and Inflammation Induced by Marathon Race - Passos, Bharbara N.; Lima, Mirthes C.; Sierra, Ana P. R.; Oliveira, Rodrigo A.; Maciel, Jaqueline F. S.; Manoel, Richelieau; Rogante, Julliane I.; Pesquero, João B.; Cury-Boaventura, Maria F. (Mediators of Inflammation, 2019)
Daily food intake is crucial to maintain health and determine endogenous fuel to practice endurance exercise. We investigated the association between quantity of macronutrient and micronutrient daily intake and inflammation induced by long-distance exercise. Methods. Forty-four Brazilian male amateurs’ marathon finishers from 30 to 55 years old participated in this study. Blood samples were collected 1 day before, immediately after, and 1 day and 3 days after São Paulo International Marathon. The serum levels of IL-6, IL-1β, IL-10, IL-8, IL-12p70, and TNF-α were measured to evaluate inflammation. Dietary intake was determined using a prospective method of three food records in the week before marathon race. Results. Marathon race promoted an elevation on IL-6, IL-8, IL-1-β, and IL-10 immediately after the race. The energy intake (EI), carbohydrate, fiber, folic acid, vitamin E, vitamin D, calcium, magnesium, and potassium intakes was below recommended. Immediately after the marathon race, we observed a negative correlation between IL-8 and daily EI, carbohydrate, fiber, fat, iron, calcium, potassium, and sodium intakes, and higher levels of IL-8 on runners with <3 g/kg/day of carbohydrate intake compared to runners with >5 g/kg/day. We demonstrated a positive correlation between daily carbohydrate intake and IL-10 and a negative correlation between TNF-α and % of energy intake recommended, carbohydrate and fiber intakes. Finally, runners with adequate EI had lower levels of IL-1β and TNF-α compared with low EI immediately after the race. Conclusion. Nutrition strategies to promote balanced diet in amateur runners seem to be as important as immunonutrition sports market. Daily food intake, mainly EI, electrolyte and carbohydrate intakes, may modulate exacerbated inflammation after endurance exercise.